THE WORKSHOP METHOD OF CONDUCTING BUSINESS ENGLISH CLASSES BY SECOND YEAR STUDENTS OF THE SPECIALTY «ENTREPRENEURSHIP, TRADE, AND EXCHANGE» - Polina S. Hrytskevyc (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article is devoted to the substantiation of efficiency of use of the technique of creative workshops with application of a technique «peer-teaching» in studying business foreign language by students majoring in Administration. The article considers one of the interactive methods, the method of conducting creative workshops, which is the most difficult of all the possible modern interactive methods when learning a foreign language. The technique of «peer-teaching» is rather briefly considered, some of its positive aspects are defined. The peculiarities of the methods of creative workshops during their preparation and conducting by students are considered in greater detail. The article identifies the positive aspects and results of creative workshops using the method of «peer-teaching» by students in the field of Administration. The methodology was considered in terms of its ability to meet the modern requirements of students. Also, it is considered as a modern methodology that is not only effective for learning a business foreign language, but also provides an opportunity to form new or consolidate the acquired professional knowledge and skills that future professionals in the field of Administration should have in order to become competitive professionals. not only on the Ukrainian but also on the international labor market. The testing of the workshop technique with the application of the «peer-teaching» method took place in a group of second-year students majoring in «Entrepreneurship, Trade and Exchange Activities» during business foreign language classes. Before implementing the methodology, students were asked about their experience of performing individual tasks during the use of old methods and after the workshops, students evaluated the workshop methodology its results in what concerns the acquired knowledge. Due to the results obtained after practical application, the article proves that the method of creative workshops together with «peer-teaching» solves some modern problems that arise when learning a foreign language: 1) achieving high performance in a short period of time; 2) ensuring the active participation of the learner in the study of the discipline; 3) ensuring the motivation and interest of the student in the discipline and learning in general; 4) the use of innovative technologies, 5) activation of the creative potential of the learner; 6) formation of the ability to apply the acquired skills in practice in future professional conditions; 7) formation of new skills and consolidation of the acquired ones that will be useful in further professional activities